The problem of pregnancy complicated by chronic kidney disease - Oleszczuk, Rafał; Kozińska, Iga; Oleszczuk, Anna; Grzebalska, Agnieszka M. (Journal of Education, Health and Sport, 2022)
Chronic kidney disease (CKD) in high-risk pregnancies is a challenge for multidisciplinary teams of doctors. Due to the fact that the disease affects both the mother and the fetus, and the course of the pregnancy. The following article reviews the literature about the interaction between pregnancy and CKD and dialysis therapy. Even pregnancy itself can lead to a worsening of kidney dysfunction. The risk of this consequence increases with the degree of renal failure, therefore renal parameters and other pregnancy test results should be monitored. On the other hand, the most common complications of chronic kidney disease in pregnancy described in the literature include pre-eclampsia, preterm labor, intrauterine growth restriction (IUGR) or low birth weight, surgical delivery by caesarean section and miscarriage. Dialysis therapy also leads to abnormalities in the course of pregnancy, and patients require constant monitoring during its course. Attention is also drawn to the high percentage of newborns requiring intensive postpartum care. Due to the risk for the fetus and mother mentioned in the article, nephrologists and gynecologists should cooperate closely from the pre-contraceptive period in order to reduce the risk of sequelae and better control of the underlying disease.